2013
DOI: 10.1055/s-0033-1345172
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory Thresholds Determined from HRV: Comparison of 2 Methods in Obese Adolescents

Abstract: The development of personalised training programmes is crucial in the management of obesity. We evaluated the ability of 2 heart rate variability analyses to determine ventilatory thresholds (VT) in obese adolescents. 20 adolescents (mean age 14.3±1.6 years and body mass index z-score 4.2±0.1) performed an incremental test to exhaustion before and after a 9-month multidisciplinary management programme. The first (VT1) and second (VT2) ventilatory thresholds were identified by the reference method (gas exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 16 publications
2
20
0
1
Order By: Relevance
“…Using an exhaustive incremental running test performed on a 200 m track, Cottin et al (8) showed that VT 1 and VT 2 could be assessed through a simple HRV monitor. Recently, these results were further confirmed in obese individuals (9), corroborating the usefulness of the HRV method to identify the first and second physiological threshold in different individuals, during different exercise modes. However, despite the support to use HRV data set when determining VT 1 and VT 2 (7)(8)(9), some aspects should be addressed.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Using an exhaustive incremental running test performed on a 200 m track, Cottin et al (8) showed that VT 1 and VT 2 could be assessed through a simple HRV monitor. Recently, these results were further confirmed in obese individuals (9), corroborating the usefulness of the HRV method to identify the first and second physiological threshold in different individuals, during different exercise modes. However, despite the support to use HRV data set when determining VT 1 and VT 2 (7)(8)(9), some aspects should be addressed.…”
Section: Introductionsupporting
confidence: 59%
“…Recently, these results were further confirmed in obese individuals (9), corroborating the usefulness of the HRV method to identify the first and second physiological threshold in different individuals, during different exercise modes. However, despite the support to use HRV data set when determining VT 1 and VT 2 (7)(8)(9), some aspects should be addressed. No study has currently verified the agreement between breakpoints identified through HRV and LT 1 and LT 2 , as no lactate measures were included in those previous studies (7,8).…”
Section: Introductionsupporting
confidence: 59%
“…However , despite revealing a significant relationship between HRV and the VT post‐training, Quinart et al . () found rMSSD slightly underestimated the VT. It may be possible that HRV stabilization points are bound by specific limits with regard to %VO 2Max whilst the VT has a far greater capacity to respon d to training, which is primarily due to the delayed onset of blood lactate at higher exercise intensities.…”
Section: Discussionmentioning
confidence: 90%
“…The results of this study may be elucidated when looking at the effects of aerobic training on vagal-related stabilization points. Two studies have investigated the effects of an aerobic intervention on both the VT and HRV stabilization points (Quinart et al, 2014;Vasconcellos et al, 2015). In both studies, obese adolescents with a low aerobic capacity were recruited and underwent an aerobic training intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation